2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318658
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based index for engagement level monitoring during sustained attention

Abstract: This paper investigates the relation between mental engagement level and sustained attention in 9 healthy adults performing a Conners' "not-X" continuous performance test (CPT), while their electroencephalographic (EEG) activity was simultaneously acquired. Spectral powers were estimated and extracted in the classical EEG frequency bands. The engagement index (β/α) was calculated employing four different cortical montages suggested by the literature. Results show the efficacy of the estimated measures in detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“…Beta band (12-30 Hz) has been linked to visual attention (Wróbel, 2000), short-term memory (Tallon-Baudry et al, 1999;Palva et al, 2011), and hypothesized to react to an increase in working memory (Spitzer and Haegens, 2017). An increase in beta power is associated with elevated mental workload levels during mental tasks (Coelli et al, 2015) and concentration (Kakkos et al, 2019). In addition, beta band activity reflects an arousal of the visual system during increased visual attention (Wróbel, 2000).…”
Section: Eeg Indicators Of Mental Workloadmentioning
confidence: 99%
“…Beta band (12-30 Hz) has been linked to visual attention (Wróbel, 2000), short-term memory (Tallon-Baudry et al, 1999;Palva et al, 2011), and hypothesized to react to an increase in working memory (Spitzer and Haegens, 2017). An increase in beta power is associated with elevated mental workload levels during mental tasks (Coelli et al, 2015) and concentration (Kakkos et al, 2019). In addition, beta band activity reflects an arousal of the visual system during increased visual attention (Wróbel, 2000).…”
Section: Eeg Indicators Of Mental Workloadmentioning
confidence: 99%
“…For the current study, three main cognitive states were assessed: focus (concentration), anxiety, and approach motivation (AM). Focus is a general measure of mental engagement evidenced by beta activity in the frontal lobe (Coelli et al, 2015). Anxiety is associated with gamma waves in the parietal and occipital lobes (Oathes et al, 2008).…”
Section: Cognitive Indicatorsmentioning
confidence: 99%
“…A participant with AM presents more high-frequency waves (or an absence of alpha activity) on the left frontal lobe than the right (i.e., frontal asymmetry). AM is related to high levels of arousal, which not only may indicate positive emotion (e.g., happiness, excitement) but could also indicate aggression or anger (Coelli et al, 2015). Previous research has validated the use of frontal asymmetry to measure AM, associating the EEG markers with self-report items, such as “I go out of my way to get things I want” and “I crave excitement and new sensations” (Amodio, Master, Yee, & Taylor, 2008).…”
Section: Cognitive Indicatorsmentioning
confidence: 99%
“…Interestingly, another study has suggested that the increase in alpha power spectrum plays an active role in preventing the distracting information into areas which retain the memory items ( Mazaheri et al, 2014 ). Moreover, previous studies have linked beta band to short-term memory ( Tallon-Baudry et al, 1999 ; Palva et al, 2011 ), elevated mental workload ( Coelli et al, 2015 ), or concentration ( Kakkos et al, 2019 ) as well as increasing in working memory ( Spitzer and Haegens, 2017 ). In the same line, the theta band is associated to increases in cognitive workload ( Fuentes-García et al, 2019 ; Diaz-Piedra et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%